UMPSA welcomes Japanese Ambassador, strengthens academic and industry ties - Nur Ezzati, Mohd Nasir (UMPSA, 2025)
PEKAN, 30 September 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received a courtesy visit from the Ambassador of Japan to Malaysia, His Excellency Shikata Noriyuki, accompanied by Ms. Masubuchi Kana, Second Secretary, at its Pekan campus this week.